MODERN APPROACHES TO ABDOMINAL DRAINAGE IN DIFFUSE PERITONITIS (World Bulletin of Public Health, 2022)
A review of domestic and foreign literature is presented, reflecting modern approaches to drainage of the abdominal cavity in generalized peritonitis. The development of new, highly effective methods of sanitation of the abdominal cavity in peritonitis is an urgent task, especially at the present stage of development of medical technologies.